2007
DOI: 10.1039/b617516c
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical atomic force microscopy study of proton conductivity in a Nafion membrane

Abstract: High membrane conductivity is one of the key parameters in polymer electrolyte fuel cell applications. We introduce an electrochemical atomic force microscopy method that provides simultaneously the surface topography of a Nafion 112 membrane and the conductivity of ion channels with an unprecedented resolution of ca. 10 nm. For given conditions, a large fraction of the channel ports is found to conduct exactly the same number of protons per unit time. This is taken as evidence for an optimum pore size and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 38 publications
8
87
0
Order By: Relevance
“…An increase in the fraction of the membrane active area with humidity is consistent with earlier observations. 28,40 However, the fraction of conductive area of Nafion shows a large area of low-current domain.…”
Section: Bulk Ionic Conductivity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the fraction of the membrane active area with humidity is consistent with earlier observations. 28,40 However, the fraction of conductive area of Nafion shows a large area of low-current domain.…”
Section: Bulk Ionic Conductivity Measurementsmentioning
confidence: 99%
“…In addition, the surface structure can affect water absorption into the membrane and influence the rate of mass-transfer processes, and thereby limit PEMFC performance. Contact angle measurements 38 and AFM imaging 17,24,25,27,[39][40][41][42] showed that the surface of the PFSA membrane is predominantly hydrophobic or non-wetting, especially at low relative humidity (RH) levels.…”
Section: Introductionmentioning
confidence: 99%
“…There is no general correlation between a higher voltage loss and a low PTFE content at the electrode. The PTFE content at the interface of the last row (segments [13][14][15][16], represented by the energy dissipation values, is almost parallel to the voltage loss. A higher dissipation value is correlated to a higher PTFE content and correlated here to a smaller voltage loss.…”
Section: Segmented Cellmentioning
confidence: 87%
“…12b the energy dissipation of anode and cathode MPL is compared for the same segments. Even though the gas diffusion media at anode and cathode are of different nature from two suppliers, the energy dissipation of gas inlet (1) and outlet (16) and those of segments 14-16 of the last row close to the outlet have a comparable value. A large difference, more precisely an almost anti-parallel behavior, is visible in the other segments analyzed by AFM (diagonal of fuel cell).…”
Section: Segmented Cellmentioning
confidence: 99%
See 1 more Smart Citation